Pin-up grrrls : feminism, sexuality, popular culture - Buszek, Maria Elena, 1971- (E-Duke books scholarly collection., 2006)
This richly illustrated history of the pin-up since its birth more than 150 years ago reveals how the development of the pin-up is intimately connected to the history of feminism.